THE ROLE OF SPEECH ACTS IN CROSS-CULTURAL COMMUNICATION (European Journal of Interdisciplinary Research and Development, 2025)
This article explores five key dimensions of how speech acts affect cross-cultural communication. By examining how cultural norms shape language use how directness and politeness vary and how social dynamics influence communicative behavior, we can develop a deeper understanding of why communication sometimes breaks down and how it can be improved.